The diagnostic odyssey of autism: a cross-sectional study of 3 age cohorts of children from the 2016-2018 National Survey of Children's Health - Allison Hanley; Quynh C. Nguyen; Deborah Golant Badawi; Jie Chen; Tianzhou Ma; Natalie Slopen (BMC, 2021)
Abstract Background Autism prevalence has increased rapidly in recent years, however, nationally representative estimates on the ages of first identification and intervention are out of date. Objectives: (1) To estimate the ages at which children with autism receive their first diagnosis, intervention plan, and developmental services; and (2) To evaluate differences in ages at events by birth cohort and sociodemographic characteristics. Methods Using cross-sectional data from the 2016-2018 National Survey of Children's Health (NSCH), we examined associations via linear regression among a sample of 2303 children aged 2-17 years old, who had ever been diagnosed with autism and either (1) ever had a plan for special education or early intervention, or (2) ever received special services to meet developmental needs. Exposures included age cohort, child, household and healthcare provider characteristics. Results Most children in the study sample (n = 2303) were over age 6 years, male, of non-Hispanic white race/ethnicity and had mild/moderate autism. Mean ages (years) at first diagnosis was 4.56 (SE = 0.13); first plan was 4.43 (SE = 0.11); and first services was 4.10 (SE = 0.11). After adjustment for exposures and survey year, the middle childhood cohort was 18 months older at first intervention (β = 1.49, 95% CI, 1.18-1.81), and adolescents were 38 months older at first diagnosis (β = 3.16, 95% CI, 2.72-3.60) compared to those in early childhood. Younger ages at events were observed among: Hispanic/Latinx as compared to white children, those with moderate or severe symptoms as compared to mild symptoms, and children who received their diagnosis from a specialist as compared to psychologists or psychiatrists. Conclusions Children with autism receive their first diagnosis, intervention plans and developmental services at younger ages than they had in the past. Future research is needed to identify the mechanisms for these improvements in early identification and intervention to accelerate additional progress.